Does the 1 Gy dose of gamma radiation impact the pork quality? - Benova, Katarina; Dvorak, Petr; Mate, Dionyz; Spalkova, Michaela; Dolezalova, Jana; Kovarik, Ladislav (Veterinarni medicina, 2021)
A nuclear accident (e.g., Fukushima), and, in particular, the transport of animals within a radiation-affected area can lead to a whole-body, or partial external irradiation, followed by oxidative stress, which could result in subsequent meat quality changes. In this experiment, live pigs were exposed to half-body irradiation by an external dose of 1.0 Gy. The caudal half of the animal's body was irradiated. After their slaughter, samples from the muscle tissue of musculus semimembranosus and musculus longissimus lumborum et thoracis at the upper margin of musculus gluteus medius (irradiated body half) and at the 3rd-4th thoracic vertebra (non-irradiated half) were collected to determine the meat quality parameters. A significant difference (P < 0.05) was observed only in the meat colour parameter (a*) in the irradiated group of pigs. If there is no internal contamination, and the half-body exposure to the external radiation dose does not exceed 1 Gy, pigs from an irradiation-affected area may be used for human consumption.
Keywords: pH; drip loss; meat colour; ionising radiation; pig